2005
DOI: 10.1074/jbc.c400606200
|View full text |Cite
|
Sign up to set email alerts
|

Are STATS Arginine-methylated?

Abstract: Transcription factors of the STAT (signal transducer and activator of transcription) family are important in signal transduction of cytokines. They are subject to post-translational modification by phosphorylation on tyrosine and serine residues. Recent evidence suggested that STATs are methylated on a conserved arginine residue within the N-terminal region. STAT arginine methylation has been described to be important for STAT function and loss of arginine methylation was discussed to be involved in interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 32 publications
(56 reference statements)
2
38
2
2
Order By: Relevance
“…To our knowledge, this is the first report on the induction of fish PRMT1 by virus infection. Recently, the significance about arginine methylation of STAT1 in IFN signalling pathway has been reassessed [50,51]. In this study, we only showed that PoPRMT was up-regulated in virus-infected FEC cells and flounder, but the link with the IFN signalling pathway was not at all addressed.…”
Section: Discussionmentioning
confidence: 65%
“…To our knowledge, this is the first report on the induction of fish PRMT1 by virus infection. Recently, the significance about arginine methylation of STAT1 in IFN signalling pathway has been reassessed [50,51]. In this study, we only showed that PoPRMT was up-regulated in virus-infected FEC cells and flounder, but the link with the IFN signalling pathway was not at all addressed.…”
Section: Discussionmentioning
confidence: 65%
“…14 Recently, the role of STAT1 methylation has been disputed in two reports. 43,44 In both reports, no conclusive evidence for STAT1 methylation could be found. In contrast to these reports and in accordance with the report by Mowen et al, 14 we consistently found in our experimental systems that the manipulation of STAT1 methylation had consequences on DNA binding of STAT1 and the induction of IFN␣ target genes (ISGs).…”
Section: Discussionmentioning
confidence: 89%
“…Recent evidence suggested that STATs are methylated on a conserved arginine residue within the N-terminal region. STAT arginine methylation has been described to be important for STAT function, and loss of arginine methylation was discussed to be involved in IFN resistance of cancer cells (34,35). IL-4 and IL-13 share receptor FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%